2010
DOI: 10.1375/jsc.5.1.7
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Perspective on Multiple Health Behaviour Change: Views of Smoking Cessation Advisors Who Promote Physical Activity

Abstract: Issues in multiple health behaviour change 2 A qualitative perspective on multiple health behaviour change: Views of smoking cessation advisors who promote physical activity Abstract There are mixed views on whether smoking cessation advisors should focus only on quitting smoking or also promote simultaneous health behaviour changes (e.g. diet, physical activity), but no studies have qualitatively examined the views and vicarious experiences of such health professionals. Semistructured interviews were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
(29 reference statements)
0
15
0
1
Order By: Relevance
“…Most exercise interventions to date have required patients to alter their substance/alcohol misuse behavior and exercise simultaneously, yet whether or not this strategy is optimal is unclear (132,133). For some individuals the challenge of changing two health behaviors simultaneously may be too demanding, whereas others may prefer to make multiple health behavior changes at once (134,135).…”
Section: Outstanding Research Questionsmentioning
confidence: 99%
“…Most exercise interventions to date have required patients to alter their substance/alcohol misuse behavior and exercise simultaneously, yet whether or not this strategy is optimal is unclear (132,133). For some individuals the challenge of changing two health behaviors simultaneously may be too demanding, whereas others may prefer to make multiple health behavior changes at once (134,135).…”
Section: Outstanding Research Questionsmentioning
confidence: 99%
“…Two participants reported that they feel happier (n = 2), a finding that simulates the findings of Shahab and West (2009). One of the participants also said that after changing his smoking behavior, he feels more alive and more active (n = 1), something that may be related to physical changes (Everson-Hock, Taylor, Ussher, & Faulkner, 2010). The majority of the participants (n = 8) said that they feel happier, with increased confidence, and having much gained, feelings that might be present after achieving their goals (Locke & Latham, 2002;Theodorakis et al, 2007).…”
Section: Leontari Et Al Psychologymentioning
confidence: 73%
“…There is limited data on how, in practice, smoking cessation specialists promote changes in multiple health behaviours and, specifically, how physical activity is encouraged [23]. This study sheds some light on this, albeit with the focus being on pregnant smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the literature cites wide variation in the timing of exercise programmes for smoking cessation, at least for smokers in general, [19]. In some instances, it has been recommended that exercise and smoking are changed sequentially, rather than simultaneously [20–23]. Of relevance here, there is evidence that smokers who have achieved abstinence have higher confidence for increasing exercise than those only planning or preparing to quit [21]; which supports the notion of increasing exercise when abstinent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation